GLOBAL SHOCKS AND THEIR IMPACT ON NIGERIA: LESSONS FROM GLOBAL FINANCIAL CRISIS - P.O Alege; T.V Ojapinwa; H.T Bello (European Scientific Journal, ESJ, 2012)
Developed a-five variable VAR model of the Nigeria economy for period 1970 . 2010, the study tested the general wisdom, \Global financial crisis does not impact on Nigeria economy.. Data were mainly sourced from both the National Bureau of Statistics (NBS) and the publication of the Central Bank of Nigeria (CBN). Augmented Dickey Fuller (ADF) and Philips-Perron (PP) tests were used in testing the null hypothesis that there is a unit root in the time series of interest. The variables considered were (1) log of GDP (2) log of FDI (3) log of REM (4) EXR and (5) CPI. Impulse-response functions were employed to examine the recovery from shocks makes full use of the within-country variation. We introduced the constant term and two lagged values of each variable in each equation and found that the impact of financial crisis on Nigeria was possible through financial links, trade links, remittances and other capital flows.This implies that the common believe about the Nigeria economy that global shocks through financial crisis does not have any impact is not quite accurate, for initially the global shocks made unstable the Nigerian economy through the macroeconomic variables understudied although after the initial instability resulting from the global shocks, the Nigeria economy then dependent less on fluctuations in the global economic crisis. We on that premise opined that the crisis presented an opportunity for Nigeria to unbalance the Nigeria economy by concentrate on leading sectors like power, education, agriculture so that the development of these sector can bring about a locomotive growth and results in balanced sector in the long run.